Trypsin inhibitors in seeds and pods of Phaseolus vulgaris/coccineus: A comparative study of shaking and ultrasonic extraction methods - Hourieh Tavakoli Hasanaklou; Barbara Pipan; Vladimir Meglič; Nevena Nagl; Lovro Sinkovič (Electronic Journal of Biotechnology, 2024)
Background: Different methods for the extraction of trypsin inhibitors in beans (Phaseolus spp.) were investigated. Two randomised complete laboratory experiments were performed, one on the seeds and one on the pods. In the first, the seeds of common bean variety KIS Marcelijan, breeding line Ref_316 × 498 and runner bean variety Bonela were examined. In the second, the fresh pods of five common beans (three breeding lines, two varieties) were analysed. Four extraction methods were used, including ultrasonic-assisted extraction (UAE) for 15 and 30 min and shaking-assisted extraction for 60 and 180 min. Results: The results showed a significant increase in trypsin inhibitor activity-related traits in UAE compared to shaking extraction, with the 15 min ultrasonic process showing better efficacy than the one with 30  min duration. In the seed experiment, the breeding line Ref_316 × 498 showed the highest Trypsin Units Inhibited (TUI) and TUI/mg sample after a 15 min UAE. In the pod experiment, the breeding line 228_4aa_ca also showed the highest TUI and TUI/mg sample after a 15 min extraction with UAE. These results underline the potential of UAE to maximise trypsin inhibitor content. In addition, remarkable correlations between TUI, TUI/mg sample and the percentage of trypsin inhibition (%TIn) were observed in both experiments. Conclusions: These results provide valuable insights into the relationship between bean genetic resources, extraction methods and trypsin inhibitor content in bean pods and seeds and serve as a basis for refining extraction protocols. The study encourages further research on the practical implications of investigated protocols for breeding programmes and agricultural practices.How to cite: Tavakoli Hasanaklou H, Pipan B, Meglič V, et al. Trypsin inhibitors in seeds and pods of Phaseolus vulgaris/coccineus: A comparative study of shaking and ultrasonic extraction methods. Electron J Biotechnol 2024;71. https://doi.org/10.1016/j.ejbt.2024.05.003.